Chemically active bed material in fluidiced-bed combustion and related processes for CO2 mitigation - Lindberg, Catrin (My University, 2022)
There are two technologies of fluidized bed combustion that recently have been developed with attempt to increase the fuel conversion and enable more efficient CO2 mitigation. These methods are called Oxygen carrier aided combustion (OCAC) and Chemical looping combustion (CLC), which both uses oxygen carrying bed material. Research have been done on both synthetic and naturally occurring oxygen carriers. Expensive synthetic materials might not be suitable when operating wilt solid fuels. These expensive materials are not attractive when operating with solid fuel, since the process implies formation of ashes and the material have to be replaced with fresh material. Researcher are currently looking for alternative materials that can be used in OCAC and CLC, which have to be cheap, accessible at large quantities and available at close distance. attention have been payed to material streams from the metallurgical industries. This study has investigated two potential materials as oxygen carriers which both are available in large quantities in the metallurgical industries in north Europe to a lower price than synthetic materials. Magnetite fines is an industrial slag product from LKAB and copper smelter slag is a by-product from Boliden AB. Experiments have been done in a lab- scale fluidized bed reactor to investigate the materials reactivity with oxygen as well as fuel conversion of syngas and methane fuel for CLC configuration. Experiments were also done for OCAC configuration to investigate the materials potential to move the combustion reactions down in the bed. Furthermore, the physical properties of each material were investigated visually to identify any significant changes during operation. Results from this study shows that magnetite fines and copper smelter slag are reactive with syngas and moderate reactive with methane in CLC configuration. Magnetite fines shows no tendency for agglomeration and sintering which was expected due to the high content of FeO and low concentration of other components commonly causing this affects. However, copper smelter slag showed tendency for agglomeration after visual inspection of the material. Further research is however necessary to fully understand how the physical properties of the materials are affected when operating as oxygen carriers in CLC and OCAC. Lab-scale experiments with longer operational time and investigation of the physical properties and changes in chemical composition are interesting for further research.
Keywords: chemical looping combustion; oxygen carrier aided combustion; oxygen carrier; magnetite fines; copper smelter slag